2006
DOI: 10.1074/jbc.m513251200
|View full text |Cite
|
Sign up to set email alerts
|

Raloxifene Increases Proliferation and Up-regulates Telomerase Activity in Human Umbilical Vein Endothelial Cells

Abstract: Vascular endothelial senescence is involved in human atherosclerosis. Telomerase activity is known to be critical in cellular senescence and its level is modulated by regulation of telomerase catalytic subunit (telomerase reverse transcriptase (TERT)) at both the transcriptional and post-transcriptional levels. Since the cardioprotective effect of estrogen itself has not been ruled out, we examined that of raloxifene, which has been classified as a selective estrogen receptor modulator, on the proliferation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 42 publications
1
17
1
Order By: Relevance
“…119 Raloxifene, a selective estrogen receptor modulator, also upregulates telomerase activity in human umbilical ECs (HUVECs). 120 In accordance with these findings, Imanishi et al found that estrogen reduces EPC senescence by increasing TERT levels in a phosphatidylinositol 3-kinase/Aktdependent manner. 121 Furthermore, estrogen stimulates in vascular ECs the production of nitric oxide, 118 which also induces telomerase activity and delays EC senescence.…”
Section: Fuster and Andrés Telomeres And Cardiovascular Diseasesupporting
confidence: 55%
“…119 Raloxifene, a selective estrogen receptor modulator, also upregulates telomerase activity in human umbilical ECs (HUVECs). 120 In accordance with these findings, Imanishi et al found that estrogen reduces EPC senescence by increasing TERT levels in a phosphatidylinositol 3-kinase/Aktdependent manner. 121 Furthermore, estrogen stimulates in vascular ECs the production of nitric oxide, 118 which also induces telomerase activity and delays EC senescence.…”
Section: Fuster and Andrés Telomeres And Cardiovascular Diseasesupporting
confidence: 55%
“…In some experiments, the membrane-permeable NF-κB transcriptional inhibitor SN50 and its inactive control SN50M (EMD Biosciences) were used to treat EC monolayers at 1 μM, a concentration previously documented to potently block NF-κB transcriptional activation in vascular ECs (Devaraj et al, 2004;Doshida et al, 2006;Iwasaki et al, 2008), including human aortic ECs (Devaraj et al, 2004).…”
Section: Measurement Of Endogenous Nf-κb Transcriptional Activity Andmentioning
confidence: 99%
“…Existing evidence has shown that ER ligands such as 17β-estradiol (E 2 ), estradiol, and raloxifene play central roles in the proliferation and migration of ERα-positive cells [6,7,8]. Therefore, E 2 was used as a positive control in the present study.…”
Section: Introductionmentioning
confidence: 99%